Longitudinal Study of Functional Reinnervation of the Denervated Skin by Collateral Sprouting of Peptidergic Nociceptive Nerves Utilizing Laser Doppler Imaging - Lakatos, Szandra; Jancsó, Gábor; Horváth, Ágnes; Dobos, Ildikó; Sántha, Péter (Frontiers in Physiology, 2020)
Restitution of cutaneous sensory function is accomplished by neural regenerative processes of distinct mechanisms following peripheral nerve lesions. Although methods available for the study of functional cutaneous nerve regeneration are specific and accurate, they are unsuitable for the longitudinal follow-up of the temporal and spatial aspects of the reinnervation process. Therefore, the aim of this study was to develop a new, non-invasive approach for the longitudinal examination of cutaneous nerve regeneration utilizing the determination of changes in the sensory neurogenic vasodilatatory response, a salient feature of calcitonin gene-related peptide-containing nociceptive afferent nerves, with scanning laser Doppler flowmetry. Scanning laser Doppler imaging was applied to measure the intensity and spatial extent of sensory neurogenic vasodilatation elicited by the application of mustard oil onto the dorsal skin of the rat hindpaw. Mustard oil induced reproducible and uniform increases in skin perfusion reaching maximum values at 2–4 min after application whereafter the blood flow gradually returned to control level after about 8–10 min. Transection and ligation of the saphenous nerve largely eliminated the vasodilatatory response in the medial aspect of the dorsal skin of the hindpaw. In the 2nd to 4th weeks after injury, the mustard oil-induced vasodilatatory reaction gradually recovered. Since regeneration of the saphenous nerve was prevented, the recovery of the vasodilatatory response may be accounted for by the collateral sprouting of neighboring intact sciatic afferent nerve fibers. This was supported by the elimination of the vasodilatatory response in both the saphenous and sciatic innervation territories following local treatment of the sciatic nerve with capsaicin to defunctionalize nociceptive afferent fibers. The present findings demonstrate that this novel technique utilizing scanning laser Doppler flowmetry to quantitatively measure cutaneous sensory neurogenic vasodilatation, a vascular response mediated by peptidergic nociceptive nerves, is a reliable non-invasive approach for the longitudinal study of nerve regeneration in the skin.